RNA-Seq Analysis Reveals the Role of Omp16 in Brucella-Infected RAW264.7 Cells - Zhou, Dong; Zhi, Feijie; Fang, Jiaoyang; Zheng, Weifang; Li, Junmei; Zhang, Guangdong; Chen, Lei; Jin, Yaping; Wang, Aihua (Frontiers in Veterinary Science, 2021)
Brucellosis is an endemic zoonotic infectious disease in the majority developing country that causes huge economic losses. As immunogenic and protective antigens at the surface of Brucella spp, outer membrance proteins (Omps) are particularly attractive for developing vaccine and could have more relevant role in host-pathogen interactions. Omp16, a homologue to peptidoglycan-associated lipoproteins (pals), is essential for Brucella survival in vitro. At present, the functions of Omp16 has been poorly studies. Here, the gene expression profile of RAW264.7 cells infected with Brucella. suis vaccine strain 2 (B. suis S2) and Omp16 mutant was analyzed by RNA-seq to investigate the cellular response immediately after Brucella entry. The RNA-sequence analysis revealed that a total 303 genes were significantly regulated by B. suis S2 24 h postinfection. Of these, 273 differential expressed genes (DEGs) were up-regulated and 30 DEGs were down-regulated. These DEGs was mainly involved in innate immune signaling pathways, including pattern recognition receptors (PRRs), proinflammatory cytokines and chemokines by KEGG analysis. In Omp16 mutant infected cells, the expression of 52 total cells genes were significantly upregulated and that of 9 total cells genes were down-regulated compared to B. suis S2 infected RAW264.7 cells. The KEGG pathway analysis showed that several upregulated genes were proinflammatory cytokines and chemokines, such as interleukin-6 (IL-6), IL-11, IL-12β, CCL2 (C-C motif chemokine), and CCL22. All together, we clearly demonstrate that Brucella Omp16 can alter macrophage immune-related pathways to increase proinflammatory cytokines and chemokines to against Brucella infection, which provide insights into illuminating the Brucella pathogenic strategies.